Characterization of smart auto-degradative hydrogel matrix containing alginate lyase to enhance levofloxacin delivery against bacterial biofilms - Islan, G. (2015)
The aim of the present work is the characterization of smart auto-degradable microspheres composed of calcium alginate/high methoxylated pectin containing an alginate lyase (AL) fromSphingobacterium multivorumand levofloxacin. Microspheres were prepared by ionotropic gelation containing AL in its inactive form at pH 4.0. Incubation of microspheres in Tris–HCl and PBS buffers at pH 7.40 allowed to establish the effect of ion-chelating phosphate on matrix erodability and suggested an intrinsically activation of AL by turning the pH close to neutrality. Scanning electron and optical microscopies revealed the presence of holes and surface changes in AL containing microspheres. Furthermore, texturometric parameters, DSC profiles and swelling properties were showing strong changes in microspheres properties. Encapsulation of levofloxacin into microspheres containing AL showed 70% efficiency and 35% enhancement of antimicrobial activity againstPseudomonas aeruginosabiofilm. Levofloxacin release from microspheres was not changed at acidic pH, but was modified at neutral pH in presence of AL. Advantageously, only gel matrix debris were detectable after overnight incubation, indicating an autodegradative gel process activated by the pH. Absence of matrix cytotoxicity and a reduction of the levofloxacin toxicity after encapsulation were observed in mammalian CHO-K1 cell cultures. These properties make the system a potent and versatile tool for antibiotic oral delivery targeted to intestine, enhancing the drug bioavailability to eradicate bacterial biofilm and avoiding possible intestinal obstructions.